Oncolytic viruses combined with immune checkpoint therapy for colorectal cancer is a promising treatment option - Ren, Yi; Miao, Jia-Meng; Wang, Yuan-Yuan; Fan, Zheng; Kong, Xian-Bin; Yang, Long; Cheng, Gong (Frontiers in Immunology, 2022)
Immunotherapy is one of the promising strategies in the treatment of oncology. Immune checkpoint inhibitors, as a type of immunotherapy, have no significant efficacy in the clinical treatment of patients with pMMR / MSS / MSI-L mCRC alone. Therefore, there is an urgent need to find combination therapies that can improve the response rate of immune checkpoint inhibitors. Oncolytic viruses are a new class of cancer drugs that, in addition to directly lysing tumour cells, can facilitate the action of immune checkpoint inhibitors by modulating the tumour microenvironment and transforming cold tumours into hot ones. The combination of oncolytic viruses and immune checkpoint inhibitors is currently being used in a number of basic and clinical studies for the treatment of tumours with exciting results. The combination of genetically modified “armed” OV with ICIs is expected to be one of the treatment options for pMMR / MSS / MSI-L mCRC. This paper will analyze the oncolytic virus that can be used to treat CRC and the current situation of ICIs in the treatment of CRC, and discuss the feasibility of combining OV with ICIs for the treat-ment of CRC in terms of the mechanism of action of OV in the treatment of tumours.